Deferiprone and Gallium-Protoporphyrin Have the Capacity to Potentiate the Activity of Antibiotics in Staphylococcus aureus Small Colony Variants - Richter, Katharina; Thomas, Nicky; Zhang, Guimin; Prestidge, Clive A.; Coenye, Tom; Wormald, Peter-John; Vreugde, Sarah (Frontiers in Cellular and Infection Microbiology, 2017)
Small colony variants (SCVs) of bacteria like Staphylococcus aureus are characterized by a reduced colony size and are linked to increased antibiotic tolerance and resistance. Their altered expression of virulence factors, slow growing properties and their ability to form biofilms make the eradication of SCVs challenging. In the context of biofilm-related infectious diseases involving S. aureus SCVs, a therapy targeting bacterial iron metabolism was evaluated. The combination of the iron-chelator deferiprone (Def) and the heme-analog gallium-protoporphyrin (GaPP), in solution and incorporated in a surgical wound gel, was tested for activity against planktonic and sessile SCVs. To this end, the activity of Def-GaPP was assessed against planktonic S. aureus SCVs, as well as against in vitro and in vivo biofilms in the colony biofilm model, an artificial wound model and a Caenorhabditis elegans infection model. While Def alone failed to show substantial antibacterial activity, GaPP and the combination of Def-GaPP demonstrated concentration- and strain-dependent antibacterial properties. Specifically, the Def-GaPP combination significantly reduced the bacterial load in an artificial wound model and increased the survival of S. aureus SCV infected C. elegans. When Def-GaPP were combined with gentamicin or ciprofloxacin, the triple combinations exceeded the antibiofilm activity of the individual compounds in the colony biofilm model. In targeting bacterial iron metabolism, Def-GaPP showed significant activity against planktonic and sessile SCVs. Moreover, Def-GaPP could potentiate the activity of gentamicin and ciprofloxacin. Delivered in a wound healing gel, Def-GaPP showed promise as a new topical strategy against infections with S. aureus SCVs.